Organic acids in pig and poultry nutrition - GIANNENAS (Η. ΓΙΑΝΝΕΝΑΣ), I. A (Journal of the Hellenic Veterinary Medical Society, 2017)
In this review article, the use of organic acids as feed additives is being examined in pig and poultry nutrition. The aim of this article was to evaluate the effect of organic acids and their salts on pig and poultry performance, to describe the organic acids used in animal nutrition, to discuss the route of administration and to investigate the mode of their action. The most widely used organic acids are formic, acetic, propionic, fumarie, citric, sorbic and butyric acid, and their salts as well. These organic acids are administered mainly through the feed, but they may be administered through the drinking water as well. Successful utilization of organic acids in pig and poultry nutrition requires knowledge of their mode of action. It is generally accepted that organic acids and their salts lower feed and gastric pH, increasing the activity of proteolytic enzymes and, thus, improving protein digestion. Besides, they reduce the buffering capacity of the feeds, resulting in reduced intestinal colonization with pathogens. They also improve the apparent digestibility of proteins and amino acids, increase the absorption of minerals and affect the composition of intestinal microflora and mucosal morphology. Relevant experimentations suggest that the organic acids improve growth rate and feed efficiency ratio in weaned piglets and fattening pigs. Also, the organic acids improve the performance of broiler chickens when used in relatively high doses, whereas, in laying hens, they improve the absorption of macroelements, like phosphorus and calcium. The present article suggests that after the recent ban on the use of the antibiotic growth promoting substances by the EU, the use of organic acids in pig and poultry nutrition appears to be an interesting alternative. However, the effect of organic acids on performance of pigs and poultry varies considerably and, thus, further research is needed for a better understanding of the mode of action and the efficacy of these compounds.